Annual mean concentrations of (non-sea-salt) sulfur, non-sea salt chlorine, fluoride, insoluble particle concentrations from an array of 19 ice cores from Antarctica and seven ice cores from Greenland - Michael Sigl; Joseph R McConnell; Nathan J Chellman; Maria Hörhold; Melanie Behrens; Birthe Twarloh; Imogen Gabriel (PANGAEA, 2025)
We report annual mean (non-sea salt) sulfur concentrations from 19 ice cores in Antarctica including WD, WDC05Q, B40, NUS08-4, NUS08-5, NUS08-7, NUS07-2, NUS07-5 and NUS07-7 (all analyzed using inductively coupled plasma mass spectrometry, ICPMS) and SP01, SP04, SPC14, DML05, DML07, DF01, DFS10, EDC96, Taylor Dome and Talos Dome (all analyzed using ion chromatography, IC). The latter are based on measurements of sulfate divided by three to derive the equivalent sulfur concentration. Additional details about the ice-core sites and analytical procedures are provided in the Supporting Data of Gabriel et al., (submitted) and in the references below citing the original publications. We report annual mean (non-sea salt) sulfur concentrations from 7 ice cores in Greenland: NEEM(2011-S1), Humboldt, B19, TUNU2013, Summit2010-composite (all by ICPMS) and EGRIP and NGRIP1 (by IC) . We further report insoluble size-resolved particle concentrations for the TUNU2013, B19 and NEEM(-2011)S1 ice cores, and insoluble size-resolved particle concentrations and non-sea-salt chlorine records from the Summit2015 ice core. These records are used alongside ice-core crypto-tephra to characterize volcanic eruption sources and to quantify volcanic sulfur injections from volcanic eruptions between 1590 and 1710 CE.